Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13075-015-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction contributes to the resistance to methotrexate treatment in rheumatoid arthritis fibroblast-like synovial cells through high mobility group box chromosomal protein 1

Abstract: BackgroundRheumatoid arthritis fibroblast-like synovial cells (RA-FLS) show resistance to methotrexate (MTX) treatment. To better understand the mechanisms of this resistance, RA-FLS and osteoarthritis fibroblast-like synovial cells (OA-FLS) were isolated and exposed to MTX. We analyzed the autophagy induced by MTX in vitro and its relationship to apoptosis.MethodsCell viability was evaluated using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and apoptosis was detected by flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 39 publications
(42 reference statements)
2
59
0
Order By: Relevance
“…Some of the mechanisms underlying drug resistance in various diseases have been established, such as DNA repair mechanisms, drug export transporters and resistance to apoptosis4041. Recent studies have found that autophagy is associated with drug resistance and that it protects cells from the cytotoxicity of chemotherapy drugs in many diseases, including cancer and inflammatory diseases3537. In our study, we found that the expression of LC3-II was increased by OMT treatment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Some of the mechanisms underlying drug resistance in various diseases have been established, such as DNA repair mechanisms, drug export transporters and resistance to apoptosis4041. Recent studies have found that autophagy is associated with drug resistance and that it protects cells from the cytotoxicity of chemotherapy drugs in many diseases, including cancer and inflammatory diseases3537. In our study, we found that the expression of LC3-II was increased by OMT treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Thin sections (60 nm) were placed on 200 mesh copper standard grids and stained with uranyl acetate and lead citrate. The ultrastructure of the cells was observed with a H-7650 transmission electron microscope (HITACHI, Ibaraki, Japan)37.…”
Section: Methodsmentioning
confidence: 99%
“…These RA FLS show signs of myofibroblast differentiation (an intermediate cell type between a smooth muscle cell and a fibroblast), such as increased collagen deposition and expression of αsmooth muscle actin, which contribute to syno vial fibrosis 97 . In RA FLS, multiple mechanisms confer resistance to programmed cell death, including increased levels of antiapoptotic factors, downregulation of proap optotic factors 98 and increased autophagy [99][100][101][102] . Ex vivo studies show that the rate of apoptosis in RA FLS has an inverse relationship to the expression of beclin1 and LC3 (REF.…”
Section: Autophagy In Rheumatic Diseasesmentioning
confidence: 99%
“…Chemotherapy cannot eliminate 100% of cancer cells partially due to intrinsic resistant phenotypes within the cancer cell population. Moreover, the tumour stroma can promote cancer cell survival and proliferation in a treatment-naïve setting and in response to treatment, which does not eliminate nonproliferating stromal cells 105 ; this intrinsic resistance might be at least partially the result of induction of autophagy rather than apoptosis in response to external agents 229 and enables stromal cells to divert their response to a nonlethal stress response.…”
Section: Effects Of Tumour Stroma On Therapymentioning
confidence: 99%